Improving Science Learning Outcomes in Theme 5 Using Google Form Media for Class V Students - Okviana Elly Candra (Universitas Sebelas Maret, 2020)
The purpose of this study was to improve student learning outcomes in Science Theme 5 Sub-theme 3 regarding ecosystem balance. This research is a Classroom Action Research (CAR) which was conducted in 2 cycles. Each cycle consists of planning, implementing, observing, and reflecting. The subjects of this study were students of class V SD Negeri 2 Nglobo in the 2020/2021 school year, totaling 20 students. Data collection techniques using observation and test techniques. The assessment instrument uses item - item and observation rubric assessment. Analysis of the data used in the study included comparative descriptive techniques, namely statistical techniques by comparing scores . The results showed that the use of google form media can improve student learning outcomes in Science Theme 5 Sub-theme 3 regarding ecosystem balance. This is evidenced by the learning outcomes in Cycle I, namely 10 students out of 20 or 50% who have not completed, while 10 students out of 20 or 50% have completed. In cycle II, there were 3 out of 20 or 15% students who had not completed, while 17 out of 20 students or 85% of the 20 students who completed it had completed. This means that student learning outcomes increase from cycle I to cycle II. The conclusion of this study is the use of google form media can improve learning outcomes Science Theme 5 Sub-theme 3 about the balance of the ecosystem in class V SD Negeri 2 Nglobo students.